Prosocial Behavior in Preschoolers: Effects of Early Socialization Experiences With Peers - Salerni, Nicoletta; Caprin, Claudia (Frontiers in Psychology, 2022)
Over the last decades, many studies had focused on the psychological outcomes of children who have received early socialization outside of the family context, highlighting that the daycare experience can both positively and negatively influence the child's social-emotional development. Despite the number of studies conducted, there is a lack of observational research on this topic. The purpose of this study is to investigate whether the early daycare experience can influence the prosocial behaviors that children exhibit during free-play social interactions with peers, focusing on their quantity and quality. In addition, the associations between the enactment of prosocial behaviors and social-emotional and behavioral competence were investigated. 160 preschoolers, 77 of whom had previously attended daycare, participated in the study and were focally observed during two free play sessions with peers. Each prosocial behavior was identified and subsequently classified using a coding scheme designed to consider the self-initiated or required origin of prosocial actions and their underlying motive. Emotion comprehension was measured using a standardized test, while social-emotional and behavioral competence was assessed using a questionnaire filled out by teachers. The main findings showed that children who had attended daycare had higher anger and aggression scores than those who had not, who, in turn, were rated by their teachers as having more internalizing behaviors. These characteristics seemed to account for the differences found in the tendency to act prosocial acts in response to a peer’s request, which was lower in children who had a previous daycare experience. Moreover, early socialization outside of the family context appeared to foster the comprehension of others’ intent to achieve emotional or instrumental personal goals and, at the same time, to reduce conventional/affiliative prosocial acts. Overall, this study suggested that the incidental effects of daycare on prosocial behavior might be canceled due to the peculiar social-emotional and behavioral characteristics of the two groups of children.